"Pure" large cell neuroendocrine carcinoma of the gallbladder. Report of a case and review of the literature. (April 2016) - Buscemi, Salvatore; Orlando, Elisabetta; Damiano, Giuseppe; Portelli, Francesca; Palumbo, Vincenzo Davide; Valentino, Alessandro; Marrazzo, Antonio; Buscemi, Giuseppe; Lo Monte, Attilio Ignazio
Abstract: Primary Neuroendocrine Tumours (NETs) of the gallbladder are rare. Among all NETs of the gallbladder, large cell neuroendocrine carcinoma (LCNEC) is exceedingly rare. In most of the cases LCNECs are combined with other histological components. We reviewed clinical presentation and management of all patients with "pure" LCNEC from published literature since the first case was published in 2000, as well as one patient from our experience. Only 7 cases of "pure" LCNEC has been described in the last 15 years, our case is the eighth. The diagnosis of gallbladder NETs is rarely made preoperatively since the presentation generally consists of non-specific symptoms including upper abdominal pain, discomfort, jaundice, weight loss. The majority of patients are identified incidentally at the time of cholecystectomy for cholelithiasis. It is not possible to differentiate preoperatively between gallbladder adenocarcinoma and gallbladder neuroendocrine carcinoma (NEC) with imaging techniques. The only curative therapeutic modality for LCNECs is a complete en bloc surgical resection, including regional lymph node clearances and hepatic lobectomy, but only in patients without multiple metastasis. LCNECs benefit from an aggressive surgical resection in combination with chemotherapy, if resectability is possible. If the tumour is non-resectable, the primary management is therefore medical and not surgical. All patients with LCNEC presented a poor prognosis with a median survival of 10 months after the initial diagnosis. Only in five patients (62.5%) a wide surgical excision was performed, while in the other cases the tumour was non-resectable or multiple liver metastases were present at diagnosis.